A Case Study of Students’ Speaking Anxiety in Learning English in the Classroom - Rohmah, Faidotur; Mohammad Kurdi Wijaya (Penerbit STKIP PGRI Bangkalan, 2025)
Anxiety is a major concern in the learning of speaking by EFL learners in an instructed language instruction situation. Speaking anxiety, despite being extensively studied, has yet to be fully understood. Keeping this in mind, this study explores the reasons of anxiety among foreign language learners, with special reference to